P160 Turning round lung cancer care in liverpool: a 15-year audit. (2nd December 2011) - Nazir, A; Aljemmali, T A; Kazmi, S M; Nazareth, D; Mohan, K; Smyth, C; Ledson, M; Walshaw, M
Abstract : Background: Liverpool has the highest incidence of lung cancer in England and Wales, and a citywide audit in 1996 identified significant deficiencies in the secondary care sector management of suspected cases. As a result of this, major reforms were made to benefit the majority of Liverpool residents in 1999, including the collaboration of competing hospitals to provide a unified service, a dedicated one stop rapid access clinic with same-day CT and bronchoscopy facilities, the employment of lung cancer specialist nurses, and parallel clinics for speedy onward referral. We have continued to refine this service, the largest in the region, and wished to compare outcomes to date. Methods: We compared the results of the service at three time points: at the 1996 audit, immediately after the inception of the service in 2001 and in 2010. Results: The results are summarised in the Abstract P160 table 1 . In addition by 2010, two thirds had CT and bronchoscopy (6 EBUS) on the same day as their rapid access clinic appointment, and 48 underwent EBUS (mean wait 5 days). The average waiting time for PET scan in 2010 was 10 days. Conclusion: This study confirms that the care of lung cancer patients in Liverpool has improved since the introduction of these new services, which we encourage other units to emulate.